Progressive resistance training for children with cerebral palsy: A randomized controlled trial evaluating the effects on muscle strength and morphology - Hanssen, Britta; Peeters, Nicky; De Beukelaer, Nathalie; Vannerom, Astrid; Peeters, Leen; Molenaers, Guy; Van Campenhout, Anja; Deschepper, Ellen; Van den Broeck, Christine; Desloovere, Kaat (Frontiers in Physiology, 2022)
Children with spastic cerebral palsy often present with muscle weakness, resulting from neural impairments and muscular alterations. While progressive resistance training (PRT) improves muscle weakness, the effects on muscle morphology remain inconclusive. This investigation evaluated the effects of a PRT program on lower limb muscle strength, morphology and gross motor function. Forty-nine children with spastic cerebral palsy were randomized by minimization. The intervention group (nparticipants=26, age: 8.3±2.0years, Gross Motor Function Classification System [GMFCS] I/II/III: 17/5/4, nlegs=41) received a 12-week PRT program, consisting of 3-4 sessions per week, with exercises performed in 3 sets of 10 repetitions, aiming at 60-80% of the 1-repetition maximum. Training sessions were performed under supervision with the physiotherapist and at home. The control group (nparticipants=22, age: 8.5±2.1years, GMFCS I/II/III: 14/5/3, nlegs=36) continued usual care including regular physiotherapy and use of orthotics. We assessed pre- and post-training knee extension, knee flexion and plantar flexion isometric strength, rectus femoris, semitendinosus and medial gastrocnemius muscle morphology, as well as functional strength, gross motor function and walking capacity. Data processing was performed blinded. Linear mixed models were applied to evaluate the difference in evolution over time between the control and intervention group (interaction effect) and within each group (time effect). The α-level was set at p=0.01. Knee flexion strength and unilateral heel raises showed a significant interaction effect (p≤0.008), with improvements in the intervention group (p≤0.001). Moreover, significant time effects were seen for knee extension and plantar flexion isometric strength, rectus femoris and medial gastrocnemius MV, sit-to-stand and lateral step-up in the intervention group (p≤0.004). Echo-intensity, muscle lengths and gross motor function showed limited to no changes. PRT improved strength and MV in the intervention group, whereby strength parameters significantly or close to significantly differed from the control group. Although, relative improvements in strength were larger than improvements in MV, important effects were seen on the maintenance of muscle size relative to skeletal growth. In conclusion, this study proved the effectiveness of a home-based, physiotherapy supervised, PRT program to improve isometric and functional muscle strength in children with SCP without negative effects on muscle properties or any serious adverse events.